2020
DOI: 10.1007/s00421-020-04507-1
|View full text |Cite
|
Sign up to set email alerts
|

A below-knee compression garment reduces fatigue-induced strength loss but not knee joint position sense errors

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…Studies have speculated that CG use enhances JPS by reducing muscle fatigue [ 21 , 22 ]. However, the results of the present study indicated that CG use failed to reduce the deleterious effects of fatigue on JPS, and absolute error increased immediately after fatigue onset; these findings are consistent with the results of a previous study [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…Studies have speculated that CG use enhances JPS by reducing muscle fatigue [ 21 , 22 ]. However, the results of the present study indicated that CG use failed to reduce the deleterious effects of fatigue on JPS, and absolute error increased immediately after fatigue onset; these findings are consistent with the results of a previous study [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…The most commonly used markers of muscle function were isometric [4,11,27,34,45, and isokinetic [40,41,54,[74][75][76][77][78][79][80][81][82][83][84][85][86][87] muscle strength. Despite this, the effects of compression on these strength markers are unclear, as a large number of studies reported either a beneficial effect [4,27,34,41,45,[66][67][68][69][70][71][72][73][82][83][84][85][86] or no effect [11, 40, 51-65, 74-81, 87].…”
Section: Performance and Muscle Functionmentioning
confidence: 99%
“…The most commonly used markers of muscle function were isometric [4,11,27,34,45, and isokinetic [40,41,54,[74][75][76][77][78][79][80][81][82][83][84][85][86][87] muscle strength. Despite this, the effects of compression on these strength markers are unclear, as a large number of studies reported either a beneficial effect [4,27,34,41,45,[66][67][68][69][70][71][72][73][82][83][84][85][86] or no effect [11, 40, 51-65, 74-81, 87]. Research investigating the effects of compression on ballistic movements is scarce, with reports of a beneficial effect on bench throw [90], but no effect on bench press barbell velocity [57] or plyometric bounds [87].…”
Section: Performance and Muscle Functionmentioning
confidence: 99%
See 2 more Smart Citations